Anticipating Permanent Persuader in Vivek Shanbhag’s Ghachar Ghochar - Shrestha, Tara Lal (International Research Journal of MMC, 2021)
Role of intellectual is often a crucial as well as controversial issue in academics and activism when an intellectual as a permanent persuader is getting more meager amidst the dominance of consumerist culture and collective crisis of the subaltern. While reading Vivek  Shanbhag’s novella Ghachar Ghochar, translated from the Kannada into English by Srinath Perur, an affirmation of intellectual’s role as a permanent persuader echoes time and again. The protagonist (unnamed narrator) is helpless, who neither could escape from collective crisis of his family nor play any role against the mounting antagonistic condition. He keeps on watching his family crisis with the thought ‘it’s not we who controls money, it’s the money that controls us. ’In the era of proliferation of the hegemony of consumerist culture, as the novella depicts, both the oppressors and oppressed are lingering in limbo beyond the rescue zone anticipating permanent persuader.